Body composition and Hashimoto disease - Ewa Malczyk; Joanna Wyka; Agata Malczyk (National Institute of Public Health - National Institute of Hygiene, 2021)
Background. Body weight or BMI do not provide any information about the content of muscle tissue, water content, body fat and its distribution in the body. Thyroid dysfunction is associated with a change in body weight, but also its composition regardless of physical activity. Objective. The aim of the study was to compare the body composition of female patients diagnosed with Hashimoto's disease (HD) and the body composition of healthy women who have never been treated before due to thyroid diseases. Materials and methods. The study involved 47 women diagnosed with Hashimoto disease (HD) and 65 women declaring good health. Body mass and height and body composition analysis using bioelectrical impedance analysis were performed using the TANITA multi-frequency segmental body composition analyzer. Variables having a distribution similar to the normal distribution were analyzed by the analysis of variance (ANOVA), otherwise the Kruskal-Wallis test was used. Results. Women with Hashimoto disease were characterized by significantly higher values of body weight, and thus BMI index, than healthy women (respectively 73.64 kg vs. 64.36 kg, p <0.0001; 27.65 kg/m2 vs. 23.95 kg/m2, p <0.001).The problem of excess body fat in the body statistically significantly more often affected women with Hashimoto disease than healthy women (44.7% vs. 13.8%, p <0.001). Conclusions. The results regarding the weight and composition of the patients treated for thyroid disease indicate the need for further in-depth analyses. Even small abnormalities of the thyroid function in the range of reference values may result in the development of many adverse changes in the body.